RESEARCHING THE COMPATIBILITY OF NITROCELLULOSE WITH GAMMA-POLYOXYMETHYLENE - Cơ (Journal of Military Science and Technology, 2021)
The article presents the research results in which VST, DSC, and TGA were used to study the compatibility of g-POM and Nitrocellulose No3. The results show that g-POM is completely compatible with Nitrocellulose No3. The findings act as an important foundation for designing and manufacturing Nitrocellulose and nitroglycerine-based energy material.